Aesthetics of intoxication - Naukkarinen, Ossi (Mimesis Edizioni, 2025)
The goal of the article is to present an overview of the aesthetics of intoxication. Various kinds of intoxicants have been widely used throughout known history, and they are closely related to the core issues of aesthetics such as art, perception, and emotions. The use of intoxicants often has aesthetic grounds, and they affect aesthetic phenomena in several ways. However, the theme has been addressed only rarely in philosophical aesthetics. After commenting on some earlier accounts, I suggest that the many faceted topic can be systematized by analyzing the relation of intoxicants and intoxication to four aesthetic perspectives: the creation of aesthetic phenomena related to intoxication, the phenomena themselves, their reception, and their context. Lastly, I compare aesthetics of intoxication to aesthetics of art and environmental aesthetics to highlight some of its typical features.
Keywords: estetiikka; alkoholi (päihteet); huumeet; päihtymys; kokemukset